Undecided voters ; Manhattan transfer ; Bayani [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Takes a look at Filipino voters preparing for the 1992 election and the SWS election survey; Manhattan Transfer, America's best vocal group, and the production of the film "Bayani" directed by Raymund Red.